POLITICAL CONFLICTS ARE INTRA-STATE IN NATURE - M. M. Abazalieva; M. A. Dyakonova (Современная наука и инновации)
Political contradictions serve as a trigger for political conflicts in the life of society. Often the end result of resolving conflicts of this kind is a change ofpolitical power and system, so such conflicts can be identified as radical. The value and ideological interests of social groups, which are in conflict with the political interests of those in power, push for decisive steps against the existing government. Thus, we can talk about conflicts, when the motive of the conflict are the contradictions between the non-basic, temporary interests and values of the conflicting agents, and significant conflicts, when there are irreconcilable contradictions between the fundamental political interests of the ruling elite and the rest of the population. Therefore, radical conflicts draw the majority of the population into the sphere of confrontation, transform the political system as a whole, changing the foundations ofpolitical institutions and public administration.